A produção acadêmica em currículo no Brasil (2004 2013) - Cesar, Edilaine (2015)
The present research aims to contribute for the state of the art of the academic productions on Curriculum within the period between 2004-2013. Its main objective is to trace a preliminary overview about the subject highlighting some aspects, dimensions and particularities identified in the process of organizing this academic works. Two specific objectives have orientated this research: a) to map the bibliographical material of Curriculum; and b) to identify the main themes of these productions. Through a qualitative and documental research it has been done a mapping of the scientific articles published in the A1, A2, B1, B2 and B3 journals extracts; of the published books; as well as in doctorate thesis and master dissertations in the whole national territory. It was possible to demonstrate an expressive growth in the number of doctorate thesis and master dissertations, articles and books on the subject of this work, mainly in the Southern region of Brazil, which is the great responsible of the major part of the productions that has been analyzed. The area of Curriculum has been consolidating itself as a scientific field that involves different kinds of knowledge and practices; meanwhile it legitimates historical, social and economic aspects of its constitution. It was also possible to foresee the Curriculum as a field of educational changes and transformations